Two new species of Tardigrada from Ecuador (South America) - Roszkowska, Milena; Gawlak, Magdalena; Draga, Mateusz; Kaczmarek, Łukasz (Zootaxa, 2019)
In two moss samples collected in El Cajas National Park (Azuay Province, Ecuador), 33 specimens and 19 eggs of a new species of Macrobiotus and 56 heterotardigrades belonging to a new Echiniscus species were extracted. Macrobiotus dulciporus sp. nov. belongs to the hufelandi group and is most similar to Macrobiotus maculatus Iharos, 1973. It differs from M. maculatus mainly based on the presence of an oral cavity armature of the patagonicus type, smooth egg chorion surface, lower number of processes on the egg circumference and some morphometric characters of the egg processes. Echiniscus hannae sp. nov. belongs to the bigranulatus group, but differs from all species in this group due to the presence of large, smooth areas on its dorsal plate.